Penegakan Hukum Terhadap Pelaku Kekerasan Siber Terhadap Perempuan Di Media Sosial - Elfa Tsalas Kurniati; Cantika Tri Julianti; Hani Zulfa Shofyanti (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2025)
The rapid development of digital technology has brought both positive and negative impacts on society, particularly for women who often become victims of cyber violence on social media. The legal issue that arises is the lack of law enforcement against perpetrators of cyber violence and the inadequate protection provided for female victims. This study examines the efforts of law enforcement against perpetrators of cyber violence against women on social media, as well as the forms of legal protection given to female victims in such cases. The research employs a normative juridical method with a statutory and conceptual approach, complemented by case studies of several reports of cyber violence in Indonesia. The findings indicate that although there are existing legal foundations, such as Law Number 19 of 2016 concerning Electronic Information and Transactions (ITE Law) and Law Number 12 of 2022 concerning Sexual Violence Crimes (TPKS Law), their implementation still faces challenges, including limited public understanding of technology, difficulties in proving cases, and the lack of gender awareness among law enforcement officers. Therefore, it is necessary to enhance the capacity of law enforcement authorities, improve regulatory frameworks, and strengthen comprehensive protection mechanisms for victims.